1993
DOI: 10.1080/00224545.1993.9713917
|View full text |Cite
|
Sign up to set email alerts
|

Acquaintance Rape: The Effect of Race of Defendant and Race of Victim on White Juror Decisions

Abstract: Racial bias appears to lead jurors in trials of stranger rape to convict Black defendants more readily and to sentence them more harshly than White defendants. It was hypothesized that jurors in an acquaintance rape case would demonstrate a different pattern of bias, based not only on the race of the defendant but also on the racial nature of the defendant-victim relationship. White American undergraduates read a trial transcript that established defendant-victim familiarity and sexual contact but was ambiguou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…Despite differences in regional location, videotaped versus written testimony, and presence versus absence of judge's instructions, the Race of Victim x Race of Defendant interaction in the present study was similar to the finding of Hymes et al (1993). In the present study, however, that interaction occurred only among the participants with high scores for authoritarianism, indicating that the more egalitarian participants may not have been as sensitive to victim and defendant race, The conclusion of Hymes et al may generalize to authoritarians in the southern United States who consider evidence in a rape trial that involves a woman who claims that she was raped by a racially dissimilar defendant: "Racial bias in juror decision making does not automatically place Blacks at a disadvantage .…”
Section: Racism In Rape Trialssupporting
confidence: 77%
See 1 more Smart Citation
“…Despite differences in regional location, videotaped versus written testimony, and presence versus absence of judge's instructions, the Race of Victim x Race of Defendant interaction in the present study was similar to the finding of Hymes et al (1993). In the present study, however, that interaction occurred only among the participants with high scores for authoritarianism, indicating that the more egalitarian participants may not have been as sensitive to victim and defendant race, The conclusion of Hymes et al may generalize to authoritarians in the southern United States who consider evidence in a rape trial that involves a woman who claims that she was raped by a racially dissimilar defendant: "Racial bias in juror decision making does not automatically place Blacks at a disadvantage .…”
Section: Racism In Rape Trialssupporting
confidence: 77%
“…Participant gender did not have a significant main effect and was not involved in any significant interactions. A pattern of means similar to that found by Hymes et al (1993) emerged among the participants with high scores for authoritarianism: F(1, 188) = 8.13, p < .01, q2 = -04, MSE = 2.10, for the Race of Victim x Race of Defendant interaction. The participants with high scores for authoritarianism were more likely to agree with a White victim's rape claim against a Black defendant (M = 3.86, SD = 1.35) than with a Black victim's rape claim against a Black defendant (M = 3.17, SD = 1.45), t(368) = 2.18, p < .05, d = 0.46.…”
Section: Racism In Rape Trialssupporting
confidence: 67%
“…Other studies concerning acquaintance rape and the effect of victim and defendant race on jury decision-making have found that defendants (Black or White) were treated most harshly and found guilty more often when their race differed from that of the victim (Hymes, Leinart, Rowe, & Rogers, 1993;Landwehr et al, 2002). This difference in research findings may be due to a different sample; whereas George and Martinez (2002) included participants of various races in their study, both Hymes et al's (1993) and Landwehr et al's (2002) samples consisted only of White participants.…”
Section: Defendant Race and Juror Decision-making In Sexual Assault Tmentioning
confidence: 87%
“…Our decision to focus on the race of the defendant and juror opens our data to alternative explanations, the most obvious of which is that the race of the victim was responsible for our findings. Race of victim has been identified by researchers (e.g., Foley & Chamblin, 1982;Hymes, Leinart, Rowe, & Rogers, 1993) and historians as an influential factor in jury decisions. Accordingly, our findings in the non-race-salient condition of Study 2 could be interpreted as indicating that White jurors are more punitive toward people who commit crimes against White victims and Blacks are punitive toward those who harm Blacks, regardless of the race of the perpetrator.…”
Section: Discussionmentioning
confidence: 99%